أسس النهوض بعلم الکلام في عصر النهضة العربية الحديثة "بديع الزمان النورسي أنموذجا" - محمد سيد محمد أحمد (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2021)
لقد دعت ظروف عصر النورسي لإعادة النظر في أسلوب منهج علم الکلام في صورته التقليدية وضرورة إيجاد أُسس جديدة بغرض النهوض به، وعصرنة هذه الآليات بما يجعلها تستجيب لظروف الواقع مؤکدا على أن الخلل الذي أصاب منهج المُتکلمين القدامى هو الاستناد على أساس واحد فقط وهو العقل المُجرد عن الوحي في البحث في القضايا الکلامية، ولقد ارتکز النورسي على مجموعة من الأسس في محاولته للنهوض بعلم الکلام تقوم على شمولية الإسلام وصلاحيته السرمدية وقدرته على استيعاب مُستجدات کل عصر من العصور ولقد اعتمد  النورسي على القرآن الکريم کأساس أولي في محاولته للنهوض بعلم الکلام. The conditions of Al-Nursi’s time called for a reconsideration of the methodology adopted in theology in its traditional form and the need to find new foundations for the purpose of promoting it, and modernizing these mechanisms in a way that makes them respond to the conditions of reality, stressing that the defect that afflicted the methodology of the old theologists was the reliance on only one basis, which is reason that is separated from revelation in researching theological issues. In his attempt to promote and advance the science of theology, Al-Nursi relied on a set of foundations that were based on the universality of Islam, its eternal validity, and its ability to absorb the developments of each era. Al-Nursi relied on the Holy Quran as a primary foundation in his attempt to advance the science of theology.